PERANCANGAN ANTARMUKA APLIKASI PERSEDIAAN STOK BARANG BERBASIS WEB DENGAN METODE PROTOTYPE PADA TOKO ALWIYA PADAHERANG - Budiman, Alwi; Mulyana, Dadan; Dwicahya Supriatman, Rian (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2025)
Poorly managed inventory can lead to financial losses for companies. An intuitive and efficient interface design is crucial for enhancing user experience in stock management applications. This research aims to design a responsive and user-friendly interface for a web-based inventory management application at Alwiya Store. The method used in this study is the prototype method, which involves stages of requirements gathering, initial design creation, prototype evaluation, and final interface design. The results show that the designed interface meets user needs with easily accessible features and clear navigation. The implementation of this interface design is expected to improve efficiency and user satisfaction in managing inventory at Alwiya Store.